2017
DOI: 10.1097/jom.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Work Functioning Impairment Scale (WFun)

Abstract: This study suggests that the WFun is useful in detecting those who have health problems affecting their work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…We previously developed and validated a self-administered questionnaire using the work functioning impairment scale (WFun) for assessment 18 . We also verified that the results of WFun assessments were correlated with the results of fit-to-work assessments conducted by occupational health nurses 19 .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…We previously developed and validated a self-administered questionnaire using the work functioning impairment scale (WFun) for assessment 18 . We also verified that the results of WFun assessments were correlated with the results of fit-to-work assessments conducted by occupational health nurses 19 .…”
Section: Introductionsupporting
confidence: 71%
“…A higher total suggests greater work functioning impairment due to health problems. A total of ≥ 21 points suggests severely impaired work functioning: a previous study found approximately 20% of employees had a WFun score of 21 points, and an assessment by occupational health nurses found these people were likely to have severely impaired work functioning and that they demonstrated high detectability with an area under the ROC curve of 0.83 19 . Cronbach’s alpha coefficient for the seven items of WFun was 0.92 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The score was calculated only when a respondent endorsed any of 13 chronic conditions 35 ) . The WFun is a seven item self-rated scale to measure work performance on the job at present, developed and validated in Japan 13 , 14 , 36 ) . The total score of WFun ranged from 4 to 28, with higher scores being indicative of greater presenteeism.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, absenteeism and presenteeism of workers due to health problems is a concern both for occupational health and productivity loss 10 ) . Well-established instruments of absenteeism and presenteeism, such as the Stanford Presenteeism Scale (SPS) 11 ) and Work Limitation Questionnaire (WLQ) 12 ) have been translated and tested for the reliability and validity in Japan 13 , 14 , 15 ) . Some instruments, such as Work Functioning Impairment Scale (WFun), were developed even originally in Japan 14 ) and extensively used in other countries 16 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation